(untitled) (Analysis in Theory and Applications, 2012)
In this paper, we investigate n-dimensional complete and orientable hypersurfaces M^n (n ≥3) with constant normalized scalar curvature in a locally symmetric manifold. Two rigidity theorems are obtained for these hypersurfaces.